Impact of an integral accompaniment program on undergraduate students’ self-perception of transversal competence development: a quasi-experimental study - Crespí, Paula; Álvarez-Montero, Santiago; Faná del Valle Villar, Amalia; Santos, Cruz; Castañeda-Vozmediano, Raúl (Frontiers in Psychology, 2026)
IntroductionIn the current healthcare context, accompaniment has emerged as a key practice for the humanization of care, distinguishing itself from other forms of support such as tutoring or coaching. This need for humanization requires the development of transversal competences, which have traditionally been marginally addressed in university education.MethodA quantitative quasi-experimental study with a pre-test/post-test design and no control group was designed to evaluate the impact of an integral accompaniment program on first-year students from various faculties, including Medicine and Health Sciences. The sample included 1,211 students from the academic years 2020–21, 2021–22, and 2022–23. The validated Basic Generic Competences Questionnaire (BGCQ) was used to measure self-perceived development of intra- and interpersonal competences.ResultsThe results showed significant improvements in both competence dimensions following the intervention (p < 0.001), with more pronounced gains in the intrapersonal dimension (Cohen’s d = 0.349) than in the interpersonal dimension (Cohen’s d = 0.146). Improvements were observed in subdimensions such as deep look, personal development, and effective communication, along with their associated competences. No significant improvements were found in the teamwork subdimension.DiscussionThe integral accompaniment program proved effective in enhancing the self-perception of key competences related to the humanization of healthcare. Although the results are promising, particularly among students from the Faculties of Medicine and Health Sciences, further studies are needed to evaluate the sustainability and long-term impact of such interventions on professional training.